2003
DOI: 10.1002/jclp.10148
|View full text |Cite
|
Sign up to set email alerts
|

Cloning the clinician: A method for assessing illusory mental health

Abstract: Self-report mental health scales cannot distinguish between genuine mental health and the facade or illusion of mental health created by psychological defenses. Shedler, Mayman, and Manis (1994) demonstrated that experienced clinicians can differentiate genuine from illusory mental health using the Early Memory Test, and that illusory mental health may be a risk factor for medical illness. This article describes the development of the Early Memory Index (EMI), a formal scoring system for the Early Memory Test,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 50 publications
0
28
0
2
Order By: Relevance
“…Two additional studies have also demonstrated that stress‐induced autonomic nervous system arousal – either SCL or coronary reactivity – is related to defense mechanism use (Shelder, Karliner, & Katz, 2003; Tang, 2002). That this relation between physiological reactivity and defense use is a function of stress is confirmed by further studies showing no relation under non‐stress conditions.…”
Section: Pillar VI the Use Of Defenses Will Be Related To Other Non‐mentioning
confidence: 99%
“…Two additional studies have also demonstrated that stress‐induced autonomic nervous system arousal – either SCL or coronary reactivity – is related to defense mechanism use (Shelder, Karliner, & Katz, 2003; Tang, 2002). That this relation between physiological reactivity and defense use is a function of stress is confirmed by further studies showing no relation under non‐stress conditions.…”
Section: Pillar VI the Use Of Defenses Will Be Related To Other Non‐mentioning
confidence: 99%
“…While assessment tools such as the YSQ provide invaluable information about such areas of relational difficulty via beliefs about others, assessment is enhanced by attention to memory retrieval and discourse processes. Information gathered through self‐report and performance‐based measures tends to vary, and these differences would themselves provide useful clinical information (Shedler, Karliner, & Katz, ; Shedler, Mayman, & Manis, ). The method used to assess SBS content in the current study could be readily included within a therapy session.…”
Section: Discussionmentioning
confidence: 99%
“…Higher scores indicate more self‐reported distress. Designed by Shedler and colleagues for IMH research, the SDS “correlates highly with many mental health scales and provides scores that are approximately normally distributed in nonclinical samples” (Shedler, Karliner, & Katz, , p. 645). In the present data set, the SDS showed strong internal consistency (alpha = 0.92) and correlated highly ( r = 0.80, p < 0.0001) with the Beck Depression Inventory (Beck, Ward, Mendelson, Mock, & Erbaugh, ).…”
Section: Methodsmentioning
confidence: 99%
“…The narrative/performance‐based measure was the Early Memory Index (EMI; Karliner, Westrich, & Shedler, ; Shedler et al, ), which is scored based on the Early Memory Test (EMT; Mayman, ). Administered in a pencil‐and‐paper fashion here, the EMT elicits elaborations of five early childhood memories.…”
Section: Methodsmentioning
confidence: 99%